BODY IMAGE AND HEALTH: A DISCUSSION ON THE PROBLEMS INVOLVING THE SEARCH FOR A “WELL-TONED” BODY. (Fiep Bulletin - online, 2016)
This article presents a discussion on the issues surrounding body image and health, drawing attention to the interpretations, sometimes misplaced, about the criteria used in order to reach body "healed", linking them to the idea of ??good health. Is divided into two parts: the first focuses on the discussion of the pursuit of the ideal body as a form of acceptance and / or social integration, with a view to disseminating that bodily health and beauty appear sometimes on condition of synonyms. The second part draws attention to the role of the professional in the field of Physical Education, crucial to rethink the issue of health, lifestyles and social, emotional and cultural dimensions involving the search for the body look "perfect".
Keywords: health; quality of life; body image